Preparing for the Future of Education: Adapting to the Technological Revolution and the World of Work - Karim Noura (Smart Society, 2024)
The  rapid  advancement  of  modern  technology,  particularly  automation  and digital communication, has transformed various industries, including education and  employment.  As  automated  tools  and  robotics  replace  human  workers  in several  sectors,  the  demand  for  a  highly  skilled  workforce  continues  to  grow. However,    there    remains    a    critical    gap    in    the    preparedness    of    young professionals  for  future  job  markets.  This  study  aims  to  analyze  the  evolving educational and workforce landscape by examining industry trends and the role of   key   stakeholders   in   shaping   educational   policies.   Using a   qualitative approach,   this   research   gathers   insights   from   experienced   educators   and industry  professionals  to  identify  essential  skills  and  competencies  required  in the   digital   era.   The   findings   highlight   the   urgent   need   for   adaptive   and interdisciplinary  education  models  that  bridge  the  gap  between  traditional curricula  and  industry  demands.  This  study  underscores  the  importance  of collaboration   between   educational   institutions,   policymakers,   and   industry leaders to foster a future-ready workforce